Environmental Communication Strategy of Food Bank Aksata Pangan in Organizational Image Development to Reduce the Food Waste in Medan - July Susanti Br Sinuraya; Syafruddin Pohan; Feni Khairifa (Formosa Journal of Social Sciences (FJSS), 2024)
This study aims to analyze the Environmental Communication Strategy of Aksata Pangan Food Bank Managers in Developing Organizational Image to Reduce Food Waste in Medan City, Obstacles experienced and how to overcome the obstacles experienced. The theory used in this study is the theory of Environmental Communication Strategy Flor & Cangara (2018). The paradigm used in this study is constructivism with the object of research being Aksata Pangan Food Bank Managers and the subject of the study is environmental communication strategy. Five (5) research informants produced saturated data and three (3) triangulation informants. Data collection techniques through in-depth interviews and observations. The results of this study found that Aksata Pangan Food Bank succeeded in identifying the main problems related to environmental communication needs through social media monitoring and news analysis. Aksata Pangan focuses on using Instagram as the main platform to reach generation Z and millennials with educational messages about environmental issues such as food waste. This effort has helped increase public understanding of environmental issues and the importance of reducing food waste, which has a positive impact on the image of the organization